노인건강문제와 간호의 방향 - 김희자(Hee Ja Kim) (지역사회간호학회지, 1998)
The elderly population will increase from 5.8% in 1996 to 12.5% in 2020. The related problems of health will also become a very important issue in the future. Therefore it is important to address the problems of geriatric nursing and geriatric health. 87.6% of the aged were ill with chronic degenerative diseases in 1994. In 1995, hospital admission rates (86.8) for those aged 60 or older were higher than that (56.3) of the total age group. Such high medical utilization will increase national health costs. For the development of geriatric nursing, active nursing intervention in various settings combined with education and research should be developed. Considering the health and welfare of the aged and the present status and views in Korea, I suggest the following: First, the health needs of the elderly in the institution, must be met by a plan that fosters geriatric nurses and programmed service development. Second, health service for the residential elderly must be provided in day care centers, short stays, nursing homes and geriatric hospitals. Geriatric nursing services should be provided in home residential areas, public health centers, public health subcenters as well as having, community health practitioners in primary health care posts and home health nurses. Third, geriatric nursing curriculum must be developed adjust to situations and culture of Korea and be included in the nursing curriculum. And gerontological nurse practitioner or geriatric specialist must be fosteraged to provide the professional care for the aged. Geriatric nursing research should be also achived for geriatric nursing improvements.